A study comparative of PSI, PSI-TOPSIS, and PSI-MABAC methods in analyzing the financial performance of state-owned enterprises companies listed on the Indonesia stock exchange - Wardany Rizky Nabila; Zahedi (Yugoslav Journal of Operations Research, 2025)
This research provides deeper insight into the advantages and disadvantages of each MCDM method in the context of evaluating SOE performance rankings. This research also shows the peformance of PSI which is used singly and integrated with other MCDM methods to determine the company’s financial health. Financial health can be reviewed through the company’s financial performance based on its financial ratios. The financial ratio criteria used include Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), and Return on Asset (ROA) as the basis for ranking. The Preference Selection Index (PSI) method is used to determine the weight of criteria and analyze the company's ranking through the identified criteria, while the Preference Selection Index-Technique for Order of Preference by Similarity to Ideal Solution (PSI-TOPSIS) and Preference Selection Index-Multi-Attributive Border Approximation Area Comparison methods (PSI-MABAC) is used to continue the weighting process on the PSI method with the results of the rankings of state-owned companies listed on the IDX. The Spearman rank correlation was determined to compare the PSI, PSI-TOPSIS, and PSI-MABAC methods. The results of the comparative analysis showed that PSI-TOPSIS and PSI-MABAC had a greater correlation compared to PSI.